Pelaksanaan Komunikasi Organisasi Di Kantor UPTP Wilayah Kabupaten Bulukumba - Suriani, Suriani; Fatmawati, Fatmawati; Mustari, Nuryanti (Universitas Muhammadiyah Makassar, 2021)
This study purposed to determine the implementation of organizational communication and supporting factors and obstacles to the implementation of organizational communication in the Samsat Office of Bulukumba Regency. This study used qualitative methods. The number of informants in this study was 9 people. Data collection techniques used interviews, observation, and documentation. The results of this study indicated that the implementation of organizational communication in the Office of Samsat Bulukumba Regency which included downward communication that had been well established so that the message delivered produced positive feedback, upward communication had been carried out well with the approach to staff in collaborating in carrying out their duties, and horizontal communication was effective by supporting each other and respect and cooperation in achieving the realization target. Supporting factors were the existence of a communicator who had high authority, friendly, firm in making decisions, and could control emotions in solving conflicts that often occured.